TINJAUAN DEBIT PADA SUMUR AIR TANAH BERBASIS POMPA AIR TENAGA SURYA - Muh. taufik Iqbal; Kushari Kushari (TEKNIK HIDRO, 2019)
To optimize the planting of rice plants, groundwater is used as a source of water so that the water needs for agricultural land can be met. Groundwater, which is a source of water, is known to contribute greatly to agricultural production, especially in the dry season. The long-term goal of this research is to increase groundwater discharge using a water pump as a controller of water distribution, alternative energy in the form of solar energy is used to drive the pump engine. During this time the pump is driven by an oil-fueled engine (BBM) which produces CO2 emissions into the air. The use of non-fuel alternative energy is expected to help reduce CO2 emissions so far. The research method begins with a survey and field survey conducted by the groundwater irrigation network in the Pare-Pare district. then search along ground waterways and mark using GPS. Measuring discharge and analyzing the performance of solar water pumps. To optimize the planting of rice plants, groundwater is used as a source of water so that the water needs for agricultural land can be met. Groundwater, which is a source of water, is known to contribute greatly to agricultural production, especially in the dry season. The long-term goal of this research is to increase groundwater discharge using a water pump as a controller of water distribution, alternative energy in the form of solar energy is used to drive the pump engine. During this time the pump is driven by an oil-fueled engine (BBM) which produces CO2 emissions into the air. The use of non-fuel alternative energy is expected to help reduce CO2 emissions so far. The research method begins with a survey and field survey conducted by the groundwater irrigation network in the Pare-Pare district. then search along ground waterways and mark using GPS. Measuring discharge and analyzing the performance of solar water pumps.